THE MEANING OF SIGNS IN â€œBREAST CANCER SURVIVORâ€™S FIRST HAIRCUTâ€ ULTA BEAUTY ADVERTISEMENT - Yugiastari; Eka Pratiwi Desak Putu; Devi Maharani Santika I Dewa Ayu (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
The meaning of signs in advertisements is very important to make it easier for the audience to understand the content and purpose of the advertisement. This study aims to discover the meaning of verbal and nonverbal signs and discover the meaning of verbal and nonverbal signs found in the "Breast Cancer Survivorâ€™s First Haircut" Ulta Beauty advertisement. Verbal signs are about text, either words or sentences while nonverbal signs are about pictures. The data were taken from Ulta Beauty Company YouTube account. The data were collected by observation method. In the research there are several theories used to analyze the data, semiotic theory by Saussure (1983) was used in analyzing verbal and visual signs in advertisement. The second is the theory of meaning proposed by Barthes (1964) to analyze the meaning of signs which consist of two layers, denotation and connotation. The last is the theory of Wierzbicka (1996) to analyze the meaning of colors. The finding shows that both verbal and visual signs have denotative and connotative meaning. Verbal and visual signs are both supporting each other to emphasize the message of the advertisement and to convince people to do particular actions Keywords: meaning, verbal signs, visual signs, advertisement